Teacher Creativity in Developing Canva-Based Language Learning Media - Ikhlas Carlan Hulu; Foster Herwin Laia; Aventrius Zebua; Yanida Bu’ulolo (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study aims to examine and enhance teacher creativity in developing Canva-based language learning media at SMK Negeri 3 ALasa. Specifically, it seeks to understand how such media can be designed to better engage students and improve learning outcomes. This research employs a Research and Development (R&D) approach using the 4D model, which includes four stages: Define (identifying needs and goals), Design (planning the media structure and content), Develop (creating and refining the media), and Disseminate (sharing the final product). The learning media were evaluated by a team of media and material experts, focusing on criteria such as visual appeal, multimedia integration, and content customization. The teachers' creativity is evidenced by the attractive visual design, varied multimedia elements, and tailored content that meets students' needs. The media achieved an 88% effectiveness score from user testing and a 92% validation score from material experts. These findings underscore the importance of integrating technology like Canva in creating innovative and engaging learning experiences. This approach not only enhances student understanding but also empowers teachers to explore creative teaching methods. The high validation scores indicate that the Canva-based learning media are effective and well-received, demonstrating significant teacher creativity and potential for broader application in educational settings.